2020
DOI: 10.1002/anie.201912705
|View full text |Cite
|
Sign up to set email alerts
|

Enriching and Quantifying Porous Single Layer 2D Polymers by Exfoliation of Chemically Modified van der Waals Crystals

Abstract: 2D polymer sheets with six positively charged pyrylium groups at each pore edge in a stacked single crystal can be transformed into a 2D polymer with six pyridines per pore by exposure to gaseous ammonia. This reaction furnishes still a crystalline material with tunable protonation degree at regular nano‐sized pores promising as separation membrane. The exfoliation is compared for both 2D polymers with the latter being superior. Its liquid phase exfoliation yields nanosheet dispersions, which can be size‐selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 75 publications
(44 reference statements)
2
34
0
Order By: Relevance
“…34,35,42 The lateral sizes of the obtained 2DP sheets rely on the size of the single crystals, and the precise thickness control and unambiguous structural denition of the exfoliated nanosheets requires additional effort. 43 Bottom-up on-surface synthesis has also enabled the preparation of various 2DP networks under ultrahigh vacuum condition. [44][45][46][47] Those strategies are generally restricted in terms of lateral size, small crystalline domains (typically tens of nanometers) and high defect density, due to the low mobility of monomers and reactivity at the solid-vacuum interfaces.…”
Section: D Polymersmentioning
confidence: 99%
“…34,35,42 The lateral sizes of the obtained 2DP sheets rely on the size of the single crystals, and the precise thickness control and unambiguous structural denition of the exfoliated nanosheets requires additional effort. 43 Bottom-up on-surface synthesis has also enabled the preparation of various 2DP networks under ultrahigh vacuum condition. [44][45][46][47] Those strategies are generally restricted in terms of lateral size, small crystalline domains (typically tens of nanometers) and high defect density, due to the low mobility of monomers and reactivity at the solid-vacuum interfaces.…”
Section: D Polymersmentioning
confidence: 99%
“… 48 Lange et al demonstrated that the scale-up of exfoliation could be achieved by shear exfoliation, ball milling or microfluidization. 49 …”
Section: Graphene and Graphene-based Nanomaterialsmentioning
confidence: 99%
“…Adapted under the terms of the CC‐BY Creative Commons Attribution 4.0 International license ( https://creativecommons.org/licenses/by/4.0). [ 85 ] Copyright 2019, The Authors, published by Wiley‐VCH. c) Chemical structures of PyVg–COF with the photos of the PyVg–COF dissolved in various solvents (top: concentrated solutions under sunlight; bottom: dilute solutions under 365 nm UV light showing the Tyndall effect).…”
Section: Monomers Encoded With Disruptive Interactionsmentioning
confidence: 99%
“…[ 84 ] The resulting 2D polymers were exfoliated by mechanical exfoliation, by stirring in γ‐butyrolactone and by sonication with sodium cholate, maintaining in the first two cases an optimal degree of crystallinity, while in the case of sonication in the presence of the surfactant a loss of crystallinity was observed. [ 85 ] 2D‐P‐1 could be transformed into a neutral pyridinic parent polymer (2D‐P‐2, Figure 15b) by exposure to gaseous ammonia, which could be exfoliated by sonication with sodium cholate with similar results in terms of quantity and quality to graphene.…”
Section: Monomers Encoded With Disruptive Interactionsmentioning
confidence: 99%